2002
DOI: 10.1021/jf020689m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultivar and Processing Method on the Contents of Catechins and Procyanidins in Grape Juice

Abstract: The aim of the presented work was to study the effect of pressing method, pasteurization, cultivar, and vintage on the content of (+)-catechin, (-)-epicatechin, and nine procyanidins in grape juice. The results showed that the concentration of these flavan-3-ols in the juice was influenced, in decreasing order of importance, by pressing method, cultivar, pasteurization, and vintage. Cold pressing without maceration was the least and hot pressing after maceration at 60 degrees C for 60 min the most effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 26 publications
8
88
2
8
Order By: Relevance
“…For Fuleki & Ricardo-Da-Silva (2003), pasteurization of grape juice increased the concentration of catechins in cold-pressed juices, but it decreased concentrations in hot-pressed juices. The concentration of most procyanidins was also increased by pasteurization.…”
Section: Thermal Processesmentioning
confidence: 97%
“…For Fuleki & Ricardo-Da-Silva (2003), pasteurization of grape juice increased the concentration of catechins in cold-pressed juices, but it decreased concentrations in hot-pressed juices. The concentration of most procyanidins was also increased by pasteurization.…”
Section: Thermal Processesmentioning
confidence: 97%
“…High proportions of flavonoids are lost during the pre-processing step when undesired parts of the product was removed or cut off. For instance, during peeling and trimming of onions it said to result in 39 per cent of flavonoids to lose 20 and great losses were noticed while peeling and dicing of tomatoes 21 . However, in another study, it was reported that cutting increased flavonol content in fresh-cut potatoes 22 and onions 23 .…”
Section: Mechanical Processes On Quercetinmentioning
confidence: 99%
“…Procyanidins are dimers resulting from the union of monomeric units of flavanols [(+)-catechin, (−)-epicatechin] by C 4 -C 8 (procyanidin B1 to B4) or C 4 -C 6 (procyanidin B5 to B8) interflavane linkage. Among grape varieties, there are differences in procyanidins concentrations, but their profile remains unchanged among grape varieties; procyanidin B1 is usually more abundant in the skin while B2 is more abundant in seeds [39]. Prodelphinidins are only present in grape skin and their monomers are [(+)-catechin, (−)-epicatechin, (+)-gallocatechin and (−)-epigallocatechin units] ( Figure 3).…”
Section: General Introductionmentioning
confidence: 99%
“…Prodelphinidins are only present in grape skin and their monomers are [(+)-catechin, (−)-epicatechin, (+)-gallocatechin and (−)-epigallocatechin units] ( Figure 3). Proanthocyanidins (procyanidins and prodelphinidins) are the major phenolic compounds in grape seed and skins [39], about 60-70% of total polyphenols are stored in grape seeds [40][41][42]. According to several published works [43,44], on average and on the basis of fresh weight, the concentrations of proanthocyanidins are as follows: total monomers ((+)-catechin and (−)-epicatechin), 2-12 mg/g in seeds and 0.1-0.7 mg/g in skins; total oligomers, 19-43 mg/g in seeds and 0.8-3.5 mg/g in skins and total polymers, 45-78 mg/g in seeds and 2-21 mg/g in skins.…”
Section: General Introductionmentioning
confidence: 99%